2021
DOI: 10.1038/s41467-020-20406-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming from managed grasslands cancels the cooling effect of carbon sinks in sparsely grazed and natural grasslands

Abstract: Grasslands absorb and release carbon dioxide (CO2), emit methane (CH4) from grazing livestock, and emit nitrous oxide (N2O) from soils. Little is known about how the fluxes of these three greenhouse gases, from managed and natural grasslands worldwide, have contributed to past climate change, or the roles of managed pastures versus natural grasslands. Here, global trends and regional patterns of the full greenhouse gas balance of grasslands are estimated for the period 1750 to 2012. A new spatially explicit la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(105 citation statements)
references
References 74 publications
4
80
0
1
Order By: Relevance
“…For this study, intact forest areas (that are unmanaged, by definition) from Potapov et al (2017) and lightly grazed grassland areas from Chang et al (2021a) were removed from the N2O totals in proportion to their presence in each inversion grid box.…”
Section: Processing Of N2o Inversions For Comparison With Inventoriesmentioning
confidence: 99%
“…For this study, intact forest areas (that are unmanaged, by definition) from Potapov et al (2017) and lightly grazed grassland areas from Chang et al (2021a) were removed from the N2O totals in proportion to their presence in each inversion grid box.…”
Section: Processing Of N2o Inversions For Comparison With Inventoriesmentioning
confidence: 99%
“…[117,118]). Lightly grazed and natural grasslands have recently been identified as large CO 2 sinks in response to rising temperatures, carbon-dioxide fertilization and nitrogen deposition [119], and changes in the management of current pasturelands have well-documented if modest potential to enhance soil carbon stocks in many locations [120][121][122]. Climate change will also require adaptation of land management practices, and it will be important to integrate mitigation and adaptation strategies [106].…”
Section: Integrating Methane Mitigation Into a Broader Contextmentioning
confidence: 99%
“…Grasslands cover about 40% of the earth's surface, providing a large number of ecosystem services (1,2). However, the intensification of land use has resulted in a worldwide degradation of species-rich forage grasslands (3,4). Recent studies have shown that inoculation with soil from a late successional stage can facilitate the establishment and growth of late-successional plant species and suppress early successional plant species at ruderal or degraded sites (5 -9).…”
Section: Main Textmentioning
confidence: 99%
“…Grasslands cover about 40% of the earth's surface, providing a large number of ecosystem services [1,2]. However, the intensification of land use has resulted in a worldwide degradation of species-rich forage grasslands and undermined their ability to support biodiversity and ecosystem functioning [3][4][5]. Recent studies have shown that inoculation with soil from a late successional stage can alter soil microbial communities and facilitate the establishment and growth of late-successional plant species [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%